271 Consistent high-quality dendritic cell vaccines produced post-chemotherapy in patients with acute myeloid leukemia for use in a Phase I/II trial. (9th November 2020) - Schnorfeil, Frauke; Geiger, Christiane; Bigalke, Iris; Josefsen, Dag; Floisand, Yngvar; Kvalheim, Gunnar; Schendel, Dolores; Tafuri, Anna; Pinkernell, Kai
Abstract : Background: A Phase I/II dendritic cell (DC) vaccine trial was completed in 20 patients with acute myeloid leukemia (AML) in complete remission or CRi after chemotherapy who were ineligible for hematopoietic stem cell transplantation (NCT02405338 ). The DC vaccines were designed to delay disease progression by mobilizing natural killer (NK) cells through secretion of IL-12(p70) and activating T cells by stimulation with WT-1 and PRAME, two prominent antigens in AML. DC vaccination was carried out in weeks 1, 2, 3, 4, 6 and monthly thereafter for 2 years. Two questions were prominent at the trial start. First, could mature DCs (mDCs) be efficiently prepared to accommodate the vaccine regimen, including use of separate DC-fractions for each antigen. Second, could suitable quality DC vaccines be generated from patients with myeloid disease, since all had received intensive chemotherapy, impairing hematopoiesis, such that several patients showed extended times for monocyte recovery in peripheral blood before being able to undergo apheresis for production. Methods: Immune monitoring tools were used to assess DC vaccines: multi-color flow cytometry for surface and intracellular protein staining, dual-color ELISpot for secretion of IL-10/IL-12, and chemokine-directed trans-well migration. Results: Adequate regeneration of monocytes occurred post-chemotherapy in all patients, allowing production of sufficient numbers of cryopreserved vaccine cells (2.5 or 5.0 × 106 mDCs/antigen/ampule) to be completed. In 15/20 patients one batch was sufficient to cover all vaccinations, while 5 patients with lower initial monocyte counts required an additional production.Phenotypic and functional parameters of patient DC vaccines were compared to cells of a healthy control (HC). Patient mDCs expressed CD83, CD40, CD80, CD86 and HLA-DR at frequencies/levels comparable to the HC. Both DC-fractions displayed intracellular protein antigen expression in most cells. Polarized secretion of IL-12(p70) without IL-10 was seen with few exceptions. Furthermore, mDCs displayed chemokine-directed migration. Detection of delayed type hypersensitivity responses post-vaccination at six weeks indicated the DC vaccines were active in vivo in all patients. Conclusions: DC vaccine production feasibility was clearly fulfilled and high quality mDCs were generated for every patient. Quantity and quality of DC vaccines did not differ in the patient groups that relapsed or remained in remission, nor in patients who succumbed to disease during the trial. DC vaccines were remarkably consistent, although originating from patients differing in age, AML subtype and receiving varied amounts of standard chemotherapy regimens. Ethics Approval: The study was approved by the responsible Norwegian ethics committee, approval number 2014/1677.